Primary fixation stability evaluation of pre-bent titanium miniplate configurations in mandibular reconstruction - Ruf, Philipp; Cebeci, Özgür; Orassi, Vincenzo; Steffen, Claudius; Duda, Georg N.; Heiland, Max; Checa, Sara; Rendenbach, Carsten (Frontiers in Bioengineering and Biotechnology, 2026)
Mandibular reconstruction is a commonly performed procedure in maxillofacial surgery with many different possible reconstructive strategies. Generally, modular fixation with miniplates has the advantage of an easier plate removal, mostly possible through an intraoral access. For patient-specific plates, the combination of reconstruction plates in the posterior area with anterior miniplates has been described as biomechanically and clinically beneficial. To our knowledge, conventional miniplates have not been biomechanically assessed in combination with reconstruction plates. Therefore, the present study aimed to evaluate combinations of pre-bent anterior miniplates with a posterior pre-bent reconstruction plate in silico as an alternative to pre-bent fixation strategies including only miniplates. The results indicate, that from a biomechanical perspective, the combination of a posterior pre-bent short reconstruction plate with anterior pre-bent miniplates is a viable alternative to fixation strategies including solely pre-bent miniplates. The process of pre-bending did not affect intersegmental strains. Analogously to patient-specific plates, the combination of a posterior pre-bent reconstruction plate with pre-bent anterior miniplates seems a surgically and biomechanically promising alternative to fixation strategies with pre-bent miniplates alone.